Kegiatan Meronce untuk Perkembangan Motorik Halus Anak Usia Dini pada Kelompok A di KB at-Taufiq Desa Cihanjawar - Chintia, Chintia Pebriyanti; Gussevi, Sofia (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Community Service Lecture (KPM) is one of the dharma activities at STAI DR. KH. EZ. Muttaqien Purwakarta. This KPM activity is a service activity carried out by final semester students to the community. In this KPM, a program is implemented, namely "Improving Children's Fine Motor Skills through Meronce". The aspect of early childhood motor physical development is one of the aspects that must be developed. Every aspect of development in a child must be considered, one of which is the development of motor aspects. The importance of AUD fine motor skills for children is to train the flexibility and coordination of the finger and hand muscles to carry out activities such as cutting, drawing, groping, and weaving. In this service, the method used is Participation Action Research (PAR). In this activity to improve the fine motor skills of early childhood, it was carried out at KB at-Taufiq Cihanjawar Purwakarta Village. The subjects in this study were group A students aged 4-5 years which totaled 13 students, consisting of 6 female students and 7 male students. The purpose of this study is to improve children's fine motor skills through meronce. With meronce activities for the development of fine motor abilities have increased. So it can be concluded that after a meronce activity is held to improve children's fine motor skills, the fine motor ability has increased.